Práticas docentes para o curso Técnico em Informática das escolas e faculdades QI: um olhar discente - Cardoso, Patricia Capitani (2013)
This dissertation is part of the research Teaching Formation, Educational Theories and Practices of the Master's Degree Post-graduate Program in Education at La Salle University Center (Unilasalle) and it has as its main goal to identify the teaching practices of the teachers of the Computer Technician Course at QI Schools and Colleges in São Leopoldo, in order to contribute for better teaching and learning processes. With this aim in view, it was primarily necessary a theoretical outlook on the being and doing of the teacher, which means, to find out the aspects related to his/her formation and the necessary competencies for teaching. Works of major authors such as Novoa (1992), Tardif (2010), Gauthier et. al (1998), Perrenoud (2000), Cabrera and La Nasa (2008) and Chickering and Gamson (1987) were used to support this study. Seeking to meet the objectives and the proposed research problem, the methodology used in this dissertation made a quantitative approach with a descriptive/exploratory goal and had as technical procedure a case study, having as research tool a questionnaire that was applied to graduates of the Computer Technician Course of QI Schools and Colleges of São Leopoldo between 2008 and 2011. For the quantitative data analysis, it was used the Descriptive Statistical Analysis of Content, oriented by Bardin (2008). From the data analysis emerged two findings. Firstly, throughout the value percentages assigned to the quantitative questions, it was clear that CE graduates appear to have a more critical point of view than SE graduates. The second evidence occurred in the general averages analysis of the related groups to the common aspects among Perrenoud, Cabrera and La Nasa and Checkering and Gamson. In this analysis was observed that none of the groups achieved one hundred percent excellence approval in the answers by the graduates. And from the qualitative data analysis was noticed the necessity by the graduates of having more proximity with the professional field, classes that can associate theory with the practice and a better pedagogical usage of the daily practice by the teachers. It highlights the necessity to rethink the teaching practices in the Computer Technician Course at QI Schools and Colleges in São Leopoldo.